Catalyzing change in middle school mathematics : initiating critical conversations. (National Council of Teachers of Mathematics, Inc., 2020)
"Catalyzing Change in Middle School Mathematics calls for all stakeholders involved in the teaching of mathematics to middle school students to critically examine the following: The identity and agency of students in middle school by being developmentally responsive while also creating and supporting a learning environment that takes into account each and every student's unique background, experience, cultural perspectives, traditions, and knowledge The inequitable structures in middle school mathematics, such as student tracking and ability grouping as well as teacher tracking, and eliminating those structures that impede students' agency and identity as capable learners and doers of mathematics Mathematics instructional practices that are equitable and attend to students as developing young adolescents, ensuring that each and every student has access to a high-quality mathematics program. How middle schools should build from a strong foundation of mathematics developed in the elementary grades, deeply engage students in the important mathematical ideas of the middle grades, and prepare students for their continued mathematics journey in high school and beyond"--